2009
DOI: 10.4076/1757-1626-2-6830
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral cavo-ilio-femoral thrombosis in an adolescent with transient anti-phospholipid antibodies and Factor V heterozygous mutation: a case report

Abstract: We report a case of bilateral cavo-ilio-femoral thrombosis in an adolescent with factor V heterozygous mutation and transient antiphospholipid antibodies secondary Varicella infection.The clinical significance of finding transient antiphospholipid antibodies in the sera of infectious disease is unclear. We here report a case of bilateral cavo-ilio-femoral thrombosis in an adolescent with newly diagnosed factor V heterozygous mutation and transient antiphospholipid antibodies secondary to Varicella infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…VZV infection-induced protein S deficiency is reported in the literature to occur by inducing the production of anti-protein S [ 26 ]. Furthermore, transient and persistent emergence of the antiphospholipid antibodies were also reported in a few patients with VZV to induce arterial and/ or venous thrombosis [ 27 , 28 ]. Our patient had transient positive anticardiolipin and lupus anticoagulant, which could have caused the thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…VZV infection-induced protein S deficiency is reported in the literature to occur by inducing the production of anti-protein S [ 26 ]. Furthermore, transient and persistent emergence of the antiphospholipid antibodies were also reported in a few patients with VZV to induce arterial and/ or venous thrombosis [ 27 , 28 ]. Our patient had transient positive anticardiolipin and lupus anticoagulant, which could have caused the thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another cross-sectional study, with 95 children enrolled, showed a transient increase of LA and aCL in 43 children following varicella infection (34). Moreover, a direct pathogenic role of VZV-induced transient increase of IgM/IgG aCL, IgM anti-b2GPI, or LA in the development of hypercoaguable state was suggested for a number of pediatric and adult cases with thrombotic or vascular complications (3537). Exposure to EBV was associated with a lupus phenotype and promoted autoimmune processes (38).…”
Section: Virusesmentioning
confidence: 99%